Implementation of Perioperative Point-of-Care Platelet Function Analyses Reduces Transfusion Requirements in Cardiac Surgery: A Retrospective Cohort Study - Wang, Lihui; Valencia, Oswaldo; Phillips, Simon; Sharma, Vivek (The Thoracic and Cardiovascular Surgeon, 2020)
Background Platelet dysfunction is a common cause of bleeding, perioperative blood transfusion, and surgical re-exploration in cardiac surgical patients. We evaluated the effect of incorporating a platelet function analyzer utilizing impedance aggregometry (Multiplate, Roche, Munich, Germany) into our local transfusion algorithm on the rate of platelet transfusion and postoperative blood loss in patients undergoing coronary artery bypass grafting (CABG) surgery.Methods Data were collected on patients undergoing CABG surgery from January 2015 to April 2017. Patients who underwent surgery before and after introduction of this algorithm were classified into prealgorithm and postalgorithm groups, respectively. The primary outcome was the rate of platelet transfusion before and after implementation of the Multiplate-based transfusion algorithm. Secondary outcomes included transfusion rate of packed red blood cells, postoperative blood loss at 12 and 24 hours, length of stay in the intensive care unit, and the hospital and mortality.Results A total of 726 patients were included in this analysis with 360 and 366 patients in the pre- and postalgorithm groups, respectively. Transfusion rates of platelets (p = 0.01) and packed red blood cells (p = 0.0004) were significantly lower following introduction of the algorithm in patients (n = 257) who had insufficient time to withhold antiplatelet agents. Receiver operating characteristic curves defined optimal cutoff points of arachidonic acid and adenosine diphosphate assays on the Multiplate to predict future platelet transfusion were 23AU and 43AU, respectively.Conclusions The introduction of a Multiplate-based platelet transfusion algorithm showed a statistically significant reduction in the administration of platelets to patients undergoing urgent CABG surgery.
Keywords: coronary artery bypass grafting surgery; CABG; blood transfusion; blood; coagulation/anticoagulation; outcomes